(untitled) (Research, Society and Development, 2022)
Deaf children can easily develop themselves through Sign Language acquisition. This language acquisition process is quite similar to the process and stages of oral language acquisition. Therefore, in the same way that a hearing child can be affected by delays and language disorders, a deaf child can also present changes in sign language that characterize atypia, whether of a primary or secondary nature. In the context of bilingual speech therapy, sign language is valued and therapy focuses on L1 so that the deaf child is able to develop normally. This case has the goal of describing the language evaluation process, in the context of bilingual speech therapy. Therefore, this study accompanied a deaf child that has complaints about atypical sign language through speech therapy follow-up with the purpose of characterizing linguistic and interactional difficulties and skills found in L1. The selected participant is a regular patient in UFRJ’s deafness ambulatory, uses sign language to communicate and is capable of understanding all the evaluation process he has gone through. The interventions carried out show the importance of assessments for the diagnosis of atypical SL and the relevance of non-standard assessments to identify, even through mediation, linguistic characteristics not evident in the standardized assessments.